Analisis Penambahan Coupling Agent terhadap Sifat Tarik Biokomposit Kulit Waru (Hibiscus Tiliaceus)-Polyester - Wirawan, Willy Artha; Widodo, Teguh Dwi; Zulkarnain, Akbar (Jurnal Rekayasa Mesin, 2018)
The aim of this research is to investigate the effect addition of silane coupling agents of Waru bast-polyester composite on tensile strength. Biocomposite is an innovation in material engineering made from the environment-friendly and potentially-developed bast fibers of Waru tree. Waru bast fibers, as reinforcement, were prepared by alkali procces employing using 6% NaOH solution for 120 minutes and then were added coupling agent with variation of 0%, 0.25%, 0.5%, 0.75% and 1.0%. The biocomposite was formed by continuous fiber arrangement using 60:40 fiber-matrix mass fractions with vacuum pressure resin infusion method. Tensile test specimens were formulated base ASTM D638-03 standard. Biocomposite investigation was performed by tensile test, while bond quality observation utilized use micro photo. The results of the study show that the highest strength of biocomposite was 401,368 Mpa on the silane coupling agent addition0.75%